Air pollution-related disease and economic burden in China, 1990–2050: A modelling study based on Global burden of disease - Dachuang Zhou; Yang Yang; Zhenping Zhao; Kejia Zhou; Di Zhang; Wenxi Tang; Maigeng Zhou (Environment International)
The disease burden of air pollution (AP) has been well-documented, yet few studies have explored its economic burden. Retrieving disease burden data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021, this study constructed a cost-of-illness (COI) model to estimate China’s economic burden of AP in 1990 and 2021 and to identify national and provincial differences, then, an age-period-cohort (APC) model was adopted to estimate trends to 2050. Results demonstrated a serious load of AP, emphasizing the necessity for intervention. Nationwide, 2021 witnessed a decline in the disease burden compared to 1990, while economic burden increased during the same period. Evidence has shown that the significant reduction in the disease and economic burden of household air pollution from solid fuels (HAP) was attributed to the adoption of clean energy, offering insights into air pollution control for low- and middle-income countries (LMICs). While ambient particulate matter pollution (AMP) emerged as the leading cause of disease and economic burden in 2021, it is predicted to endure, particularly in provinces like Heilongjiang, Hebei, and Liaoning. Northern and inland regions bear a higher burden than southern and coastal do. Population aging exacerbates these challenges, urging stricter controls on AMP and protections for the elderly, thereby mitigating health and economic impacts caused by AP.